2019
DOI: 10.1136/bcr-2018-228530
|View full text |Cite
|
Sign up to set email alerts
|

Case of retroperitoneal necrotising fasciitis: a rare and deadly spread

Abstract: Necrotising fasciitis (NF) is a potentially lethal spread of infection that is uncommonly seen within the province of surgery. Seen mostly in the extremities and the perineal regions, it has been reported rarely to involve the retroperitoneal space and presents with a spectrum of symptoms and signs as such. Literature supports classification of NF based on the microbes involved. Irrespective of the aetiology and the causative organism, NF remains a serious surgical emergency with high morbidity and mortality n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Sugimoto et al reported a case of a 58-year old hypertensive man who developed extensive retroperitoneal necrotizing fasciitis resembling Fournier's gangrene from which Streptococcus anginosus was isolated [8] . Ikram et al presented a case of necrotizing fasciitis in the retroperitoneal space secondary to a perineal infection, which showed heavy growths of Corynebacterium and mixed anaerobic species [9] . The main organisms detected in our case were Klebsiella, Escherichia coli and mixed anaerobic species making it a polymicrobial type of necrotizing fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al reported a case of a 58-year old hypertensive man who developed extensive retroperitoneal necrotizing fasciitis resembling Fournier's gangrene from which Streptococcus anginosus was isolated [8] . Ikram et al presented a case of necrotizing fasciitis in the retroperitoneal space secondary to a perineal infection, which showed heavy growths of Corynebacterium and mixed anaerobic species [9] . The main organisms detected in our case were Klebsiella, Escherichia coli and mixed anaerobic species making it a polymicrobial type of necrotizing fasciitis.…”
Section: Discussionmentioning
confidence: 99%